Lipoprotein (a) concentrations, apolipoprotein (a) phenotypes, and peripheral arterial disease in three independent cohorts - Laschkolnig, Anja (Oxford University Press, 2014)
AIMS: The relevance of lipoprotein(a) [Lp(a)] concentrations and low-molecular-weight (LMW) apo(a) phenotypes in peripheral arterial disease (PAD) has only been investigated by few studies. Therefore, we analysed this association in three independent cohorts and performed a Mendelian Randomization approach using instrumental variable regression. METHODS AND RESULTS: Lp(a) concentrations, apo(a) phenotypes, and one SNP in the LPA gene (rs10455872) were measured in the CAVASIC study, including 241 male patients with intermittent claudication and 246 age- and diabetes-matched controls as well as in the two population-based studies KORA F3 (n = 3184) and KORA F4 (n = 3080). In KORA F3/F4, 109/80 persons suffered from intermittent claudication, 200/144 from PAD, and 128/103 showed an ankle–brachial index (ABI) <0.9. In CAVASIC, adjusted logistic regression analyses revealed significant associations between an increase of log-Lp(a) per one standard deviation (SD) (OR = 1.28, P = 0.02) as well as LMW apo(a) phenotypes and symptomatic PAD (OR = 1.65, P = 0.03). Linear regression models with continuous ABI showed a significant association in the combined analyses of KORA F3/F4: an increase in log-Lp(a) per one SD (β = −0.006, P = 0.005) and the presence of LMW apo(a) phenotypes (β = −0.011, P = 0.02) or the minor allele of rs10455872 (ß = −0.016, P = 0.03) were associated with a decrease in ABI in the fully adjusted linear and instrumental variable regression models. CONCLUSION: Analyses in three independent populations showed significant associations of Lp(a) concentrations, LMW apo(a) phenotypes, and rs10455872 with PAD. This points to a causal relationship between Lp(a) and PAD since the genetically determined apo(a) phenotypes and SNP alleles are indeed associated with PAD.